Risk Management of Occupational Health and Safety Program: (Case Study at PT. X) - Tuddiana, Imama; Hardati, Ratna Nikin; Trianti, Khoiriyah (International Journal of Social Science and Community Service, 2024)
The aim of this study is to comprehend PT. X's management of Occupational Health and Safety (OHS) risk, the execution of OHS programs, and the challenges encountered by the organization. This study utilizes a qualitative approach. It employs three methods for data collection: documentation, interviews, and observations. The Miles and Huberman interactive model is utilized for data analysis in this research. The research results reveal that OHS risk management at PT. X involves the identification, analysis, evaluation, and control of OHS risks. The implementation of OHS at PT. X involves the establishment of OHS policies and the provision of health assurances and safety equipment. The hindrances to the OHS program at PT. X include the attitudes and behaviors of workers who are hesitant to wear personal protective equipment and the company's failure to re-conduct socialization on the importance of OHS.